PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ATHENA TAGAYA SURABAYA - S.Y, ratnaningsih; sutrisno, didit (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRAKDevelopment of technology and information to make PT. Athens Tagaya Surabaya engaged in cleaning services have wanted to improve its ability to organize the existing resources, especially human resources into the frame the better, because the resource management that will either save cost, improve performance accelerate the achievement of goals at once will create good relations and employee loyalty towards the organization of the company. The work environment within the company will be able to change the attitudes and behavior of human resources in order to increase labor productivity and to compete and face the challenges of the future. Besides the motivational factor is required with employee expectations can carry out work environment that has been applied in a company with a commitment as a duty and responsibility so that progress can be felt by both sides. The purpose of this study was to determine: 1) the simultaneous effect of Work Environment and Work Motivation on Employee Performance. 2) partial effect Work Environment and Motivation on Employee Performance. The subjects were employees of PT. Athens Tagaya Surabaya as many as 40 people. Data was collected using a questionnaire. Statistical method used is multiple linear regression analysis. Conclusion: (1) There is significant influence between Working Environment and Work Motivation simultaneously the Employee Performance PT. Athens Tagaya Surabaya. Environment Variables Work and Work Motivation together contributed 57.9% of the Employee Performance. (2) There is significant influence partially on the Work Environment Employee Performance. Work Environment Variables give partial effect to the Employee Performance by 32.49%. There is a significant relationship between working motivation partially on Employee Performance PT. Athens Tagaya Surabaya. The motivation variable influence to variable 16.65% Employee Performance.Â Kata Kunci : Work Environment, Employee Motivation, Employee PerformanceÂ